An investigation in the use of preposition in the written english of first year centre for language students of IIC - Fazlinda Hamzah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The ability to use prepositions accurately is crucial among ESL learners since it reflects their language competency. It has also been noted that acquiring the correct use of prepositions is not a simple task for ESL learners. This study sought to analyse the errors related to the target prepositions in, on and at in the written English of first year Centre for Language (CFL) students of International Islamic College (IIC), to identify the possible sources of preposition errors and to find out if mother tongue interference is a source of errors related to the target prepositions. Fifty essays written by first year Malay students of IIC were used in this study and the topics of the essays centred on common human concerns such as family, friendship and marriage. The errors related to the prepositions in, on and at were identified and explained. Next, the sources of errors were analysed and plausible explanations given. The findings of the study show that the students' problem was mostly with the preposition in, followed by at and lastly on. It was also found that native language interference was probable source of errors related to the prepositions in, on and at..